2014
DOI: 10.1155/2014/721505
|View full text |Cite
|
Sign up to set email alerts
|

Daily Intake of Probiotics with High IFN-γ/IL-10 Ratio Increases the Cytotoxicity of Human Natural Killer Cells: A Personalized Probiotic Approach

Abstract: A personalized probiotic microfluidic chip system has been established and used to screen the probiotics which had the highest value of IFN-γ/IL-10 or IL-10/IFN-γ among six probiotics, including L. paracasei BRAP01, L. acidophilus AD300, B. longum BA100, E. faecium BR0085, L. rhamnosus AD500, and L. reuteri BR101. One hundred volunteers were included and their PBMCs were collected and stimulated by the six probiotics. People who belonged to the IFN-γ group took the probiotics that exerted the highest ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…18 It has been reported that NK cell activity could be enhanced by certain strains of probiotics in humans. 19 In this review, we examine the effects of probiotics on gut immunity, specifically describing how NK cell activity and subsequently innate immunity are affected by the addition of certain probiotic strains into a human daily diet.…”
Section: Probioticsmentioning
confidence: 99%
“…18 It has been reported that NK cell activity could be enhanced by certain strains of probiotics in humans. 19 In this review, we examine the effects of probiotics on gut immunity, specifically describing how NK cell activity and subsequently innate immunity are affected by the addition of certain probiotic strains into a human daily diet.…”
Section: Probioticsmentioning
confidence: 99%
“…According to Kitazawa and Villena [24] the immunobiotic strain Lactobacillus rhamnosus CRL1505 acts by modulating of TLR3-mediated immune response against viral challenge in respiratory tract. Several immunobiotics strains have been screened for their immunomodulatory activities by Ho et al [87] , Lactobacillus paracasei BRAP01 and Lactobacillus acidophilus AD300 associated with higher value of IFN-γ/IL-10 were found to enhance the NK cytotoxicity in human blood. Immunobiotics such as Lactobacillus rhamnosus and Bifidumbacterium lactis HN019 that exhibit anti-inflammatory proprieties could be helpful for patients with COVID-19 [82] .…”
Section: Immunobiotics Intervention In Gut-lung Pathwaysmentioning
confidence: 99%
“…But with the passage of time, probiotics efficiency seem to decrease, gathering scientist's attention. [76] Oral administration of fermented milk with Lactobacillus helveticus R389 demonstrated immunoregulatory response in breast cancer bearing mice and suggested its use as immune adjuvant therapy to protect against malignancies. [77] Yazdi et al not only reported an increase in inferon (IFN)-γ and IL-2 levels but also shows enhanced NK cell activity in selenium nanoparticles enriched Lactobacillus plantarum-treated mice.…”
Section: Association Of Bacteria With Breast Cancermentioning
confidence: 99%